Sister broods in the spruce bark beetle, Ips typographus (L.) - Davídková, Markéta (Jihočeská univerzita, 2014)
The aim of this thesis was to elucidate the establishment of sister broods in the spruce bark beetle, Ips typographus (L.), at three localities of different elevation in Sumava Mountains. Fecundity, sex ratio in the offspring, regeneration feeding, development of reproductive organs, re-emergence rate and other ecophysiological topics were studied as well.
Sister broods in the spruce bark beetle, Ips typographus (L.)
Keywords: lýkožrout smrkový; sesterská přerojení; ekofyziologie; spruce bark beetle; sister broods; ecophysiology